Analysis of Teachers’ Challenges in Implementing Arabic Language Learning Evaluation in Madrasah Aliyah and It’s Implementative Solutions - Isop Syafei; Padilah Rizky Putri Rambe; Syahrul Jaki Ramadhan; Saad Abu Ramdani (Gunung Djati Conference Series, 2026)
This study aims to describe the challenges faced by teachers in planning, implementing, and following up on Arabic language learning evaluation in Madrasah Aliyah, as well as to formulate applicable solutions for schools. The research employs a descriptive qualitative approach, with primary data obtained from interviews, observations, and teachers’ assessment documents, and secondary data derived from curriculum guidelines and supporting literature. Data were collected through semi-structured interviews, classroom observations, and analysis of evaluation tools. The data were then analyzed through processes of reduction, presentation, and conclusion drawing, with triangulation used to ensure validity. The findings indicate that teachers experience difficulties in developing skill-based assessment instruments, face limitations in conducting authentic assessments, and lack systematic follow-up procedures. Contributing factors include teachers’ competencies, limited facilities, curriculum demands, and the diverse abilities of students. The study also reveals that these challenges affect the accuracy of assessment and students’ achievement of learning competencies. Applicable solutions include providing guidance in instrument development, utilizing simple media, diversifying assessment formats, and implementing structured remedial and enrichment mechanisms.